Polemismo, tradición y modernidad en Ḥasdai Crescas (II). Monográfico editado y coordinado por José Antonio Fernández López y Alexander Fidora - Fernández López, José Antonio; Fidora, Alexander (Anales del Seminario de Historia de la Filosofía, 2024)
The study of these fundamental questions, which were in part already addressed in a first monographic section dedicated to Ḥasdai Crescas in the last issue of this journal, is expanded in its perspective and scope by the articles contained in this second dossier.